Pengembangan Kawasan Ekowisata Pulau Maitara Kota Tidore Kepulauan - Wiwin Prasetaji Sadik; Rahmawati Rahman; Ilham Yahya (Journal of Urban Planning Studies, 2021)
Abstract. The purpose of this study is to formulate directions for the development of the Maitara Island Tourism area, Tidore Archipelago City as an Ecotourism area. The main problem then produces sub-problems or research questions about "what is the strategic direction for the development of Maitara Island as an ecotourism area in the City of Tidore Islands?" This type of research is qualitative with the research approach used is applied research which includes surveys. Field Observation, Agency and Community Interview Surveys Furthermore, data processing techniques and data analysis were carried out using SWOT analysis. The results of this study produced strategies on how to take advantage of the tourism potential of Maitara Island such as the potential for coral reefs, mangrove forests and white sand beaches for planning a tourism-based area ecotourism on Maitara Island, involving community participation in tourism development on Maitara Island to improve the economy of the local community and how to take advantage of the strategic location of Maitara Island to serve as i a leading tourist area in the City of Tidore Islands.